Work-Life Ideologies: The Contextual Basis and Consequences of Beliefs About Work and Life - Leslie, Lisa M.; King, Eden B.; Clair, Judith A. (Academy of Management Review, 2019)
Work-life scholars have devoted considerable attention to understanding the relationship between work and life but surprisingly little attention to understanding how individuals think about the relationship between work and life. We propose that individuals hold three work-life ideologies, which we define as beliefs about how work and life are related: a fixed (versus expandable) pie ideology, a segmentation (versus integration) ideology, and a work (versus life) priority ideology. Beliefs about the world come, in large part, from the world itself. We therefore advance propositions regarding the contextual antecedents of work-life ideologies; exposure to contexts that prime scarcity, boundaries, and market forces increase the extent to which individuals hold fixed pie, segmentation, and work priority ideologies, respectively. For each prime we also provide four examples of objective contextual features—one each at the family, organizational, community, and societal level of analysis—that make the relevant prime salient and shape the associated work-life ideology. Finally, we propose that work-life ideologies are consequential because they affect individuals’ work-life preferences and how they make sense of demands and resources, which, in turn, affect work-life conflict and enrichment. Our research advances understanding by expanding theory regarding the critical role of cognition in navigating work and life.